1994
DOI: 10.1159/000261988
|View full text |Cite
|
Sign up to set email alerts
|

Delayed Effect of Wheat Starch in Foods on the Intraoral Demineralization of Enamel

Abstract: There is considerable evidence for an association between dental caries and food starches. However, the intraoral utilization of starch may be quite complex, giving rise to conflicting results. Demineralization induced by unsweetened cookies was examined in an intraoral model system that utilized palatal appliances containing blocks of bovine enamel. The enamel surfaces were covered with either a filter paper disc to trap sugars or a layer of Streptococcus mutans to metabolize the sugars and bring about enamel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

1996
1996
2015
2015

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 16 publications
1
20
0
Order By: Relevance
“…Some methods in particular, such as the indwelling plaque pH method, seem to be very sensitive to even low sugar foods that are not normally implicated in dental caries, and may accentuate Zero food retention, creating a worst case scenario [Edgar and Geddes, 1986]. Starches have also been shown to have cariogenic potential in many model systems, including in vitro models [Renz and Bibby, 1989], plaque acidity models [Lingström et al, 1993], animal caries models [Firestone et al, 1982;Mundroff et al, 1990] and in situ caries models [Brudevold et al, 1988;Kashket et al, 1994;Lingström et al, 1994;Pollard, 1995]. However, definitive data in humans are lacking [Lingström et al, 2000], suggesting that some degree of caution should be used when interpreting results from these models.…”
Section: Other Evidencementioning
confidence: 99%
“…Some methods in particular, such as the indwelling plaque pH method, seem to be very sensitive to even low sugar foods that are not normally implicated in dental caries, and may accentuate Zero food retention, creating a worst case scenario [Edgar and Geddes, 1986]. Starches have also been shown to have cariogenic potential in many model systems, including in vitro models [Renz and Bibby, 1989], plaque acidity models [Lingström et al, 1993], animal caries models [Firestone et al, 1982;Mundroff et al, 1990] and in situ caries models [Brudevold et al, 1988;Kashket et al, 1994;Lingström et al, 1994;Pollard, 1995]. However, definitive data in humans are lacking [Lingström et al, 2000], suggesting that some degree of caution should be used when interpreting results from these models.…”
Section: Other Evidencementioning
confidence: 99%
“…An intra-oral method has been developed that follows de-or remineralization of blocks of human enamel or dentin, or of bovine enamel, that are covered by a layer of S. mutans cells so as to mimic dental plaque (Brudevold et al, 1985;Kashket et al, 1994). Studies with this model have shown that raw and cooked wheat starch induced negligible and mild demineralization, respectively (Brudevold et al, 1985), whereas boiled gelatinized wheat starch gels (10, 15, or 20% starch) induced significant demineralization and significant pH drops (minimum pH of 4.8-5.0) (Brudevold et al, 1988).…”
Section: Other Studiesmentioning
confidence: 99%
“…For example, the temperature at which rice starch begins to gelatinize increases from 85.3 to 111.3°C when the water-starch ratio drops from 2.0 to 0.75 (French, 1983;Lund, 1983Lund, , 1984. The starches in baked products such as bread are prepared with low levels of water and appear to be only partially gelatinized (Osman, 1967 (Neff, 1967;Imfeld, 1983;Kashket et al, 1994Kashket et al, , 1996. Maltose fermentation requires bacterial adaptation under certain conditions (Kashket et al, 1994).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because of the adhesiveness of starchy foods, they are easily retained in the dentition [Lingström and Birkhed, 1993], and thus a continuous supply of carbohydrate derived from salivary starch digestion could help to maintain a low plaque pH for a long time [Lingström and Birkhed, 1993;Kashket et al, 1994]. To address the adhesiveness of starchy foods as well as the diffusion of starch and acidic end products within dental plaque, research using biofilm models could be valuable [Kashket et al, 1994;Duarte et al, 2008].…”
Section: Discussionmentioning
confidence: 99%